Geochronology of the Phanerozoic granitoids in northeastern China - Wu, F.; Sun, D.; Ge, W.; Zhang, Y.; Grant, Matthew; Wilde, Simon; Jahn, B. (Pergamon-Elsevier Science Ltd, 2011)
Northeast (NE) China is characterized by immense volumes of granitic rocks, exposed over an area of200,000 km2. Although the precise geochronological framework was not clear, it was considered thatmost of them were emplaced during the Paleozoic, when numerous tectonic blocks amalgamated. Overthe past decade, we have selected 370 samples for zircon U–Pb dating in order to constrain the spatialand temporal distribution of granitoids in the area. These data, combined with 63 ages obtained by otherresearchers, indicate that Paleozoic granitoids are not as widely distributed in the area as previouslythought. In the eastern part of the area, granitoids in the Zhangguangcai Range were mostly emplacedduring the Jurassic (150–190 Ma) with a small amount in the Paleozoic, whereas granitoids in theNadanhada Terrane, the easternmost part of NE China, have an emplacement age of 115 Ma. In the west, granitoids exposed in the Great Xing’an Range were mainly formed during the Early Cretaceous(120–135 Ma) with some in the Paleozoic, and those in the Erguna Massif, the westernmost part of NEChina, were emplaced during the Jurassic (160–190 Ma). Based on the temporal–spatial distribution ofthese granitic rocks, it is suggested that the Paleozoic granitoids were formed during various stages from oceanic subduction to block amalgamation in the Central Asian Orogenic Belt (CAOB). It is proposed that the Jurassic granitoids in the Zhangguangcai Range were probably related to Paleo-Pacific plate subduction west of the Jiamusi Massif (block). This subduction resulted in regional lithospheric thickening, and subsequent delamination of the thickened lithosphere due to its gravity instability in the Early Cretaceous. Unlike other areas in the Central Asian Orogenic Belt, NE China was significantly affected by subduction of the Paleo-Pacific ocean, and can be considered as one of the most important areas of the eastern Asian active continental margin during the Mesozoic.